Correlates of quit intentions among current Nigerian smokers: Evidence from the 2012 Global Adult Tobacco Surveys (GATS). (2020)
INTRODUCTION Approximately 3.1 million people use tobacco in Nigeria contributing to the burden of tobacco-related morbidity and mortality. However, many tobacco users who have tried to quit have been unable to do so at the first try, but may succeed or give up after multiple attempts. The transtheoretical model helps by classifying those with quit intentions into preparation, contemplation and precontemplation stages. These assist in the development of targeted interventions towards smokers in each stage for more effective results. There is limited evidence about cessation and quitting behaviour in the Nigerian context. This study aimed to explore the factors related to the intention to quit among current tobacco smokers in Nigeria using the transtheoretical model. METHODS The study was a secondary data analysis of the Nigeria 2012 Global Adult Tobacco Survey (GATS). The survey included non-institutionalized men and women aged ≥15 years. Data were analysed using SPSS version 21. The primary outcome variable was smoking quit intention. The correlates of quit intentions were determined for a p<0.05. RESULTS A total of 429 current smokers were mostly in precontemplation (64.7%) while 14.9% were in the preparation stage. Exposure to anti-tobacco media messages was associated with increased quit attempts, however, knowledge about the harmful effects of tobacco was associated with fewer quit intentions. Very few had access to cessation therapy and none had accessed a quitline. Male respondents were 9 times more likely to have a quit intention compared to females (OR=9.615; 95% CI: 1.449–1.478). Respondents with primary education were nearly three times more likely to have quit intentions than those with tertiary education (OR=2.991; 95% CI: 2.930–3.053). CONCLUSIONS While attention is on smoking prevention, most smokers in Nigeria are not considering quitting. There is a need for targeted interventions to reach smokers at various stages.